Protective mat consisting of a pp piece and a steel piece and assembly method

CN122747342APending Publication Date: 2026-09-15KUNSHAN KERSEN SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610856677.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-09-15

Smart Images

  • Figure CN122747342A_ABST
    Figure CN122747342A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of machining, and particularly discloses a protective pad composed of a PP piece and a steel piece, which comprises a glass fiber reinforced PP base and a galvanized steel support framework embedded in the PP base in an interference mode, the outer circumferential surface of the PP base is a multi-factor compensation size surface which is formed through secondary finishing under a pre-assembly constraint state, all the machined surfaces of the PP base are integrated treatment surfaces of dry ice deburring and surface activation, the matching end surfaces of the PP base and the steel support framework are provided with circumferential fool-proof and rotation-stopping double positioning features which are formed through synchronous milling, the alignment error of the double positioning features is less than or equal to 0.02 mm, and the alignment accuracy retention rate after secondary disassembly is greater than or equal to 95%, the application initiates a secondary finishing process under a pre-assembly constraint state, establishes a coupling size compensation formula and an online self-adaptive correction mechanism which cover multiple factors such as thermal expansion, moisture absorption and stress release, and the outer circumferential size deviation of the PP base is controlled within + / -0.01 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of machining technology, specifically to a protective pad composed of PP parts and steel parts and its assembly method. Background Technology

[0002] Protective pads are core sealing and vibration damping components of automotive air conditioning systems. They are mainly installed at the connection between the fan and the housing, and at the interfaces of air conditioning pipes. They play a crucial role in sealing against leaks, reducing vibration and noise, and preventing external debris from entering the air conditioning system. Their dimensional accuracy, bonding strength, and environmental adaptability directly affect the operating efficiency, comfort, and service life of the air conditioning system. With the rapid development of the new energy vehicle industry, the requirements for the quietness, energy efficiency ratio, and durability of vehicle air conditioning systems are constantly increasing. Traditional protective pads can no longer meet the requirements for high-precision assembly and long-term stable use in a wide temperature range of -40℃ to 85℃ and under strong vibration environments.

[0003] Currently, the industry generally adopts a protective pad structure that combines glass fiber reinforced PP with galvanized steel. This structure utilizes the lightweight and corrosion-resistant properties of PP material with the high-strength support properties of steel to achieve complementary performance. However, there are still many technical problems that need to be solved in the existing technology.

[0004] The existing process uses separate precision machining followed by assembly, without comprehensively considering the coupled effects of multiple factors such as thermal expansion, moisture absorption, and processing stress release. The dimensional deviation of the finished product can reach more than ±0.05mm. After assembly, the gap between the finished product and the shell is uneven, which can easily lead to sealing failure, reduced energy efficiency, and abnormal operating noise. At the same time, there is a lack of a systematic stress control system. The internal stress generated by raw materials, stamping, and processing is not completely eliminated. The finished product is prone to dimensional creep during use, and the long-term accuracy decay is serious.

[0005] Current deburring methods for PP parts mainly employ mechanical grinding and chemical etching, which can cause secondary damage and environmental pollution, and cannot simultaneously achieve surface activation. While dry ice deburring technology has been applied, the industry has not yet established quantitative standards for process parameters and deburring rates and surface energy, relying instead on manual experience. Furthermore, the low intrinsic surface energy of PP material results in insufficient bonding strength between PP and steel components, with axial pull-out forces typically below 80N. This makes them prone to debonding under temperature cycling and long-term vibration, failing to meet the usage requirements of new energy vehicles for over 10 years.

[0006] Existing PP substrates and steel support frames mostly employ a single boss-notch positioning structure, and are assembled and aligned after separate processing. The alignment error is typically greater than 0.05mm, and the positioning accuracy is essentially lost after secondary disassembly and reassembly. Under the vibration and torque of vehicle operation, the components are prone to relative rotation, leading to sealing failure and abnormal noise, resulting in poor reliability. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a protective pad composed of PP parts and steel parts, and an assembly method thereof, thus solving the problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a protective pad composed of PP and steel components, comprising a glass fiber reinforced PP matrix and a galvanized steel support frame interference-fitted into the inner ring of the PP matrix; the outer circumferential surface of the PP matrix is ​​a multi-factor compensation dimensional surface formed by secondary precision machining under pre-assembly constraint; all machined surfaces of the PP matrix are treated with dry ice deburring and surface activation in an integrated manner; the mating end faces of the PP matrix and the steel support frame are provided with circumferential anti-foolproof and anti-rotation dual positioning features formed by synchronous milling, the alignment error of the dual positioning features is ≤0.02mm, and the alignment accuracy retention rate after secondary disassembly and assembly is ≥95%.

[0009] Preferably, the target machining dimension of the multi-factor compensated dimension surface Calculated using the following multi-factor coupling compensation formula: ; in: The nominal design dimensions are for the outer peripheral surface of the PP substrate; Design tolerances are provided for the outer peripheral surface of the PP substrate in one direction. The coefficient of linear expansion of glass fiber reinforced polypropylene (PP) is given, with a range of values. ; The total temperature difference between the machining environment and the vehicle's maximum operating limits; The equivalent temperature difference coefficient is used to account for non-uniform thermal expansion; This represents the maximum stress-release deformation of PP after machining under constrained conditions. This is the compensation amount for time-dependent moisture absorption expansion deformation. , RH represents the hygroscopic expansion coefficient of PP, and RH represents the annual average relative humidity of the operating environment. The PP moisture absorption equilibrium time constant is taken as 120–180 h. This refers to the cumulative duration of use of the protective mat since it was put into service. This is the dimensional compensation amount resulting from nozzle distance correction. , The vertical distance from the dry ice spray nozzle to the PP substrate surface is in mm. The value represents the amount of microplastic deformation on the PP surface caused by dry ice deburring, ranging from 0.01 to 0.02 mm. The apparent size reduction caused by the micro-nano texture formed by dry ice surface activation is 0.005–0.01 mm. This is the deformation compensation correction coefficient, with a value ranging from 0.1 to 0.2.

[0010] Preferably, the dry ice deburring and surface activation integrated treatment meets the following criteria: ; in, The total number of burrs with a height ≥ 0.01 mm before deburring. This represents the number of burrs remaining after deburring. This refers to the dry ice injection pressure. The speed of the dry ice spray gun is measured in mm / s. This represents the vertical distance from the nozzle to the PP substrate surface, in mm. The value range is 100–150 mm; The value represents the average diameter of the dry ice particles, expressed in μm, and ranges from 300 to 500 μm.

[0011] Preferably, the dual positioning feature is an L-shaped foolproof positioning groove with an alignment accuracy of [missing information]. The following formula is used to determine this: ; in, Let be the geometric center coordinates of the L-shaped positioning groove on the PP substrate. The coordinates are the geometric center coordinates of the L-shaped positioning groove on the steel support frame. The coordinate system is established with the intersection of the component axis and the mating end face as the origin.

[0012] Preferably, the dimensional stability of the finished product meets the following criteria: ; The temperature cycling conditions were as follows: within the range of -40℃ to 85℃, the temperature change rate was 5℃ / min, with each high and low temperature held for 1 hour, for a total of 150 cycles; and during the cycling process, a frequency of 10–55 Hz and a power spectral density of 0.02 g were superimposed. 2 Random vibrations at / Hz These are the measured dimensions of the PP matrix periphery after cycling.

[0013] A protective pad composed of PP and steel parts is prepared and assembled in a manner that includes four stages: raw material pretreatment and surface treatment, pre-assembly and finishing, positioning detection and adhesive curing, and finished product detection and warehousing.

[0014] Preferably, the raw material pretreatment and surface treatment stage includes the following steps: S0 Raw Material Pre-screening and Batch Consistency Control: Melt index testing is performed on each batch of glass fiber reinforced PP raw materials, and the melt index deviation is controlled to be ≤ ±0.5g / 10min; zinc layer thickness uniformity testing is performed on galvanized steel coils, and the zinc layer thickness deviation is ≤ ±1μm; S1 Raw Material Incoming Inspection: Testing the linear expansion coefficient of PP material. hygroscopic expansion coefficient and moisture absorption equilibrium time constant , as the input parameter of the compensation formula; S1.1 Raw material pre-drying treatment: Place the PP rods in an 85℃ hot air circulating drying oven and dry for 8 hours to reduce the moisture content to below 0.05%; S2PP annealing pretreatment: The dried PP rods are placed in an 80℃ constant temperature oven for annealing for 4 hours, and then cooled to 23℃ at a rate of 1℃ / h and stored in a desiccator for 24 hours to completely eliminate internal stress and residual moisture. S3 steel pretreatment: After the galvanized steel coil is flattened, it is leveled to a flatness of ≤0.05mm, and stamped to obtain a steel support frame blank with 3 V-shaped positioning notches and an annular glue storage groove; S3.1 Stress-relieving annealing of steel parts: Place the steel support frame blank in a constant temperature oven at 180℃ for annealing for 2 hours to eliminate the internal stress of stamping; S3.2 Steel Surface Cleaning: Use an ultrasonic cleaner to clean the steel support frame blank to remove stamping oil and metal debris, and then dry it with hot air. S4PP rough machining: PP billet is obtained by CNC turning PP bar stock. A 0.4mm finishing allowance is reserved on the outer perimeter. Three positioning bosses with elastic barbs are milled on the inner ring, which correspond one-to-one with the V-shaped positioning notch of the steel part. S5 coarse deburring: Use a nylon brush to clean the macroscopic burrs on the PP blank and the steel support frame blank; S5.1 Pre-calculation of dry ice process parameters: According to the surface energy formula in claim 3, with mm μm is the initial value, and the following equations are combined... Select injection pressure With movement speed Theoretical value; S5.2 Dry ice process parameter verification: Take 3 PP test pieces, perform dry ice treatment according to theoretical parameters, and test the surface energy and deburring rate. If the requirements are not met, fine-tune the parameters until they are qualified. The final S6 dry ice process parameters were determined: Based on the verification results, the dry ice injection pressure for this batch was determined. Movement speed Nozzle distance and the diameter of dry ice particles ; S7 dry ice integrated treatment: Dry ice treatment is performed on the machined surface of the PP blank according to the final determined parameters, and the residual debris is blown away with 0.2MPa compressed air after treatment. S7.1 Dry ice treatment effect test: Randomly select 5% of PP blanks, test surface energy and deburring rate, and reprocess unqualified parts.

[0015] Preferably, the pre-assembly and finishing stage includes the following steps: S8 pre-assembly press fitting: A servo press is used to press the steel support frame into the inner ring of the PP blank at a speed of 5mm / s. After the positioning boss is engaged with the positioning notch, the pressure is held for 10s. The axial movement is checked to be ≤0.02mm, and the pre-assembled component is obtained. S8.1 Real-time monitoring of pressing force: The pressing force curve is collected in real time during the pressing process. The peak pressing force should be controlled within the range of 80 to 120 N. Components that exceed the range are marked as unqualified. S9 Pre-assembled Component Modal Testing: Impact modal testing is performed on the pre-assembled components to identify their first-order natural frequencies. ,like If the pressure is Hz, adjust the pressing force and press again; S9.1 Modal Analysis: For components with a first natural frequency close to 200Hz, analyze their mode shapes. If the mode shape shows relative torsion between the PP matrix and the steel support frame, then re-press-fit. S10 Secondary Clamping and Alignment: Clamp the pre-assembled components onto the five-axis CNC machine, using the inner hole and end face of the steel support frame as the positioning reference, with an alignment accuracy of ≤0.005mm; S10.1 Clamping Deformation Detection: After clamping, use a dial indicator to check the deformation of the PP substrate end face. Subsequent processing can only proceed if the deformation is ≤0.003mm. S11 Machining Dimension Calculation: Substitute the multi-factor coupling compensation formula according to claim 2 into the current batch... , , Ambient temperature and humidity, distance from dry ice nozzle Calculate the target machining dimension based on the dimensional deviation feedback value from the previous batch. Import the CNC machining program; S11.1 Machining parameter optimization: Based on the machinability of PP material, the cutting speed is determined to be 120-150 m / min, the feed rate is 0.1 mm / r, and the depth of cut is 0.2 mm; S12 Synchronous Finishing: Turning the outer circumferential surface of the PP substrate to the desired depth using optimized machining parameters. Then, simultaneously mill the L-shaped anti-foolproof positioning groove on the same end face of the PP substrate and the steel support frame; S12.1 Process temperature monitoring: Use an infrared thermometer to monitor the temperature of the cutting area in real time. If the temperature exceeds 60℃, pause the process and resume when the temperature drops below 40℃. S13 Online Accuracy Inspection and Feedback: The outer perimeter dimensions of the PP substrate are detected in real time using a laser diameter gauge. If the deviation exceeds ±0.01mm, the part is marked and the compensation coefficient is triggered. The adaptive correction is given by the following formula: , Take 0.05; S13.1 Real-time Temperature Compensation: During online detection, the ambient temperature is collected synchronously. Temperature compensation is applied to the measurement results of the laser diameter gauge. The compensation formula is as follows: ,in The linear expansion coefficient of the optical glass in the laser diameter gauge is given by [value]. ; S13.2 Dimensional Deviation Statistical Analysis: Perform statistical analysis on the dimensional deviations of all machined parts in this batch, calculate the average value and standard deviation. If the standard deviation exceeds 0.005mm, adjust the CNC machining parameters. S14 Stress Relief and Micro-Vibration Aging: The finished components were placed in an environment of 23±1℃ and 45±5%RH and subjected to micro-vibration with a frequency of 20~50Hz and an amplitude of 0.08mm for 6 hours. S14.1 Vibration Aging Energy Density Control: During the vibration aging process, the vibration energy density is input. Should meet ,in Amplitude (unit: mm) Vibration frequency (unit: Hz). The vibration time is expressed in seconds. S14.2 Real-time monitoring of dimensional stability: The outer circumference dimension is checked every 2 hours. The change in the dimension is ≤0.005mm after two consecutive measurements. If the requirement is not met after 6 hours, the vibration aging time is extended to 8 hours.

[0016] Preferably, the positioning detection and adhesive curing stage includes the following steps: S15 Positioning Accuracy Detection: Detect the alignment of the L-shaped anti-foolproof positioning groove according to the formula in claim 4. mm, if it is not up to standard, it will be reworked; S15.1 Anti-rotation performance test: For components with qualified positioning accuracy, apply a circumferential torque of 5 N·m and test whether relative rotation occurs. If no rotation occurs, it is qualified. S16 Disassembly, Cleaning and Plasma Activation: The pre-assembled components are disassembled along the axial direction. After wiping the mating surfaces with anhydrous ethanol, the inner ring surface of the PP matrix is ​​treated with atmospheric pressure plasma at a power of 300W for 10s. S16.1 Plasma treatment uniformity test: Nine points are evenly selected on the inner ring surface of the PP matrix using a contact angle measuring instrument, and the surface contact angle is measured. The uniformity is qualified if the contact angle deviation is ≤ ±2°. S16.2 Surface Energy Verification: After plasma treatment, the surface energy of the inner ring surface of the PP matrix should be ≥60mJ / m 2 Defective parts are re-treated with plasma. S17 Automatic Adhesive Application: An adhesive dispensing robot is used to uniformly apply acrylic structural adhesive to the mating surfaces, with the adhesive layer thickness controlled between 0.03 and 0.05 mm. S17.1 Adhesive layer thickness uniformity control: During the dispensing process, the dispensing speed... With glue output satisfy ,in This is the volume correction factor for the adhesive solution, with a value ranging from 0.95 to 1.05. This refers to the width of the adhesive application, in mm. The target adhesive layer thickness is expressed in mm. S17.2 Adhesive application quality inspection: The continuity and integrity of the adhesive application trajectory are detected by a visual inspection system. No adhesive breaks or overflows are considered qualified. S18 Secondary Assembly Pressure Holding: Press the steel support frame into the PP matrix according to the corresponding position of the L-shaped anti-foolproof positioning groove, apply 0.2MPa axial pressure and hold for 30min; S18.1 Control of adhesive overflow during pressing: During the pressing process, the amount of adhesive overflow should be controlled within 80% to 100% of the volume of the annular adhesive storage tank. Insufficient or excessive overflow is marked as unqualified. S18.2 Real-time monitoring of adhesive layer curing: The adhesive layer curing process is monitored in real time using an ultrasonic flaw detector. The pressure holding can only be released when the adhesive layer curing degree reaches more than 90%. S18.3 Excess Adhesive Cleaning: After the pressure holding is completed, use a special tool to clean up any excess adhesive that has overflowed, ensuring that there is no residual adhesive on the mating surfaces; S18.4 Static Curing: After removing excess adhesive, place the module in an environment of 23±1℃ and 45±5%RH for 2 hours until the adhesive layer is completely cured.

[0017] Preferably, the finished product inspection and warehousing stage includes the following steps: S19 Finished Product Inspection: After secondary assembly, the alignment error of the L-shaped anti-foolproof positioning groove is re-inspected to be ≤0.03mm, and temperature cycling and random vibration verification are carried out under the conditions described in claim 5. S19.1 Pull-out force test: Randomly select 1% of the finished products and test the axial pull-out force. A pull-out force ≥120N is considered qualified. S19.2 Sealing test: Assemble the protective gasket onto the standard air conditioner housing, apply a pressure difference of 500Pa, and the leakage rate is ≤0.5L / min to be considered qualified; S19.3 Debris blocking efficiency test: Standard dust with a particle size of 0.3 to 0.5 mm is used for testing. A debris blocking efficiency of ≥99.95% is considered qualified. S19.4 Sound insulation performance test: The sound insulation of the protective pad at a frequency of 2000Hz is tested using a sound level meter. A sound insulation of ≥3dB is considered qualified. S19.5 Appearance Inspection: The appearance of the finished product is inspected using a visual inspection system. The product is considered qualified if there are no defects such as scratches, deformation, or missing materials. S20 Packaging and Warehousing: All qualified finished products are individually packaged in anti-static bags, labeled with the product model, batch number, and production date, before being put into storage.

[0018] Preferably, the dimensional deviation feedback value of the previous batch mentioned in step S11 is the sum of the values ​​of all qualified parts in the previous batch. average And use Bayesian optimization to optimize the performance of five consecutive batches. Perform a smooth update; the update formula is as follows: , The learning rate ranges from 0.02 to 0.08.

[0019] Preferably, the PP matrix is ​​made of 12wt% glass fiber reinforced PP with a tensile strength ≥35MPa and a heat distortion temperature ≥120℃; the steel support frame has a zinc coating thickness of 8~12μm, and shows no rust after 48h salt spray test; the annular glue storage tank has a depth of 0.1~0.2mm and a width of 0.5mm; and the axial pull-out force of both is ≥120N.

[0020] Preferably, the gap between the protective pad and the air conditioner housing after assembly is ≤0.07mm, the airflow disturbance reduction rate is ≥18%, the ≥0.3mm debris blocking efficiency is ≥99.95%, and the sound insulation at 2000Hz frequency is ≥3dB.

[0021] This invention provides a protective pad composed of PP parts and steel parts, and an assembly method thereof, which has the following beneficial effects: 1. This invention pioneers a secondary finishing process under pre-assembly constraints, establishing a coupled dimensional compensation formula and online adaptive correction mechanism that covers multiple factors such as thermal expansion, moisture absorption, and stress release. This controls the dimensional deviation of the PP substrate to within ±0.01mm, the finished product assembly gap to ≤0.07mm, and the airflow disturbance reduction rate to ≥18%. Simultaneously, it adopts an L-shaped anti-foolproof positioning groove with pre-assembly synchronous milling, achieving a positioning alignment error to ≤0.02mm, a secondary disassembly and assembly accuracy retention rate to ≥95%, and no relative rotation when a 5N·m torque is applied. This solves the problems of poor dimensional stability and sealing failure and abnormal noise caused by relative rotation of components in traditional processes.

[0022] 2. This invention establishes an integrated quantitative process system for dry ice deburring and surface activation, which can remove all burrs with a height ≥0.01mm and increase the surface energy of PP to ≥38mJ / m 2 This process avoids secondary damage from mechanical grinding and environmental pollution from chemical corrosion, increasing production efficiency by more than 25%. By combining full-process stress control of "raw material annealing - steel stress relief - micro-vibration aging" with atmospheric pressure plasma activation and precise adhesive layer control technology, the axial pull-out force between PP and steel frame is ≥120N, which is 50% higher than the traditional process. After 150 cycles of high and low temperature vibration, the dimensional change rate is ≤0.05%, meeting the requirements for the entire life cycle of new energy vehicles.

[0023] 3. This invention establishes a full-chain quality control system from raw material entry to finished product warehousing, strictly controlling the batch consistency of raw materials and key parameters of the processing process, ensuring that the standard deviation of product batch size is ≤0.005mm and the scrap rate is reduced by more than 30%; the prepared protective pad has a debris blocking efficiency of ≥99.95% and a sound insulation of ≥3dB at a frequency of 2000Hz, with a comprehensive upgrade in performance, and can be widely used in fields with stringent requirements for precision and durability, such as air conditioning for new energy vehicles, rail transit, and home appliances. Attached Figure Description

[0024] Figure 1 This is an axial sectional view of the protective pad; Figure 2 A graph showing the relationship between dry ice process parameters and performance; Figure 3 This is a flowchart of the entire assembly process for the protective pad. Figure 4 This is a comparison chart of the key performance characteristics of the present invention and traditional processes. Detailed Implementation

[0025] The technical solutions of the present invention will be clearly and completely described below in conjunction with the technical solutions of the present invention. The described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0026] This embodiment provides a protective pad composed of PP parts and steel parts and its assembly method, aiming to solve the technical problems of poor dimensional stability, low positioning accuracy, insufficient bonding strength and poor durability of existing PP-steel composite protective pads, and to meet the high-precision assembly and long-term stable use requirements of new energy vehicle air conditioning systems in a wide temperature range of -40℃ to 85℃ and strong vibration environment.

[0027] The protective pad of the present invention includes a glass fiber reinforced PP matrix and a galvanized steel support frame that is interference-fitted into the inner ring of the PP matrix. The two are compositely connected by interference fit and structural adhesive bonding.

[0028] like Figure 1 As shown, the protective pad is a ring-shaped composite structure. In the axial direction, the glass fiber reinforced PP matrix is ​​wrapped around the outer periphery of the galvanized steel support frame, and the inner ring surfaces of the two are interference fit surfaces. The mating end face of the steel support frame is provided with a ring-shaped glue storage groove to accommodate the acrylic structural glue overflowing during assembly. The same end face of the PP matrix and the steel support frame is simultaneously milled with L-shaped anti-foolproof positioning grooves, with at least one set evenly distributed in the circumference, to achieve the dual functions of anti-foolproof and anti-rotation.

[0029] The PP matrix is ​​made of 12wt% glass fiber reinforced PP, with a tensile strength ≥35MPa and a heat distortion temperature ≥120℃, combining lightweight, corrosion resistance and certain structural strength. The steel support frame is made of galvanized steel and stamped. The galvanized layer on the surface is 8-12μm thick and shows no rust after 48 hours of salt spray testing. It provides high-strength support and resistance to deformation. The end face of the frame is provided with an annular glue storage groove with a depth of 0.1-0.2mm and a width of 0.5mm to accommodate the glue that overflows during assembly and ensure the uniformity of the glue layer.

[0030] The core structural features of the protective pad are as follows: Multi-factor compensated dimensional surface: The outer peripheral surface of the PP substrate is a multi-factor compensated dimensional surface formed by secondary precision machining under pre-assembly constraint state, and its target machining dimension is... The calculation uses a multi-factor coupling compensation formula to comprehensively compensate for the influence of various factors such as thermal expansion, hygroscopic expansion, stress release, and surface treatment deformation on the finished product dimensions. ; Meaning and range of values ​​for each parameter: The nominal design dimensions of the outer peripheral surface of the PP substrate are determined according to the air conditioner housing assembly requirements. The unidirectional design tolerance for the outer peripheral surface of the PP substrate is typically 0.03–0.05 mm. The coefficient of linear expansion of glass fiber reinforced polypropylene is given by [value]. The specific value needs to be determined through incoming raw material testing. This is the total temperature difference from the machining environment (23±1℃) to the vehicle's extreme operating temperature (-40℃~85℃), usually taken as 125℃; The equivalent temperature difference coefficient, which takes into account the non-uniform thermal expansion between the PP matrix and the steel skeleton, was obtained through extensive experimental verification. The maximum stress release deformation after PP machining under constrained conditions is determined through preliminary testing of this batch of PP materials, and is typically taken as 0.01 to 0.02 mm. The time-dependent moisture absorption expansion deformation compensation amount is calculated using the following formula: ; in RH represents the hygroscopic expansion coefficient of PP, and RH represents the annual average relative humidity of the operating environment. The moisture absorption equilibrium time constant of PP is 120-180h. This refers to the cumulative duration of use of the protective mat since it was put into service. This is the dimensional compensation amount resulting from the dry ice jet nozzle distance correction. , The vertical distance from the nozzle to the PP surface (100-150mm). The value is 0.01 to 0.02 mm, representing the amount of microplastic deformation on the PP surface caused by dry ice deburring. The apparent size reduction caused by the micro-nano texture formed by dry ice surface activation is 0.005–0.01 mm. This is the deformation compensation correction coefficient, initially set to 0.1–0.2, and subsequently adaptively corrected through batch size deviation feedback.

[0031] Dry ice integrated treatment: All machined surfaces of the substrate undergo integrated dry ice deburring and surface activation treatment. This process simultaneously achieves high-precision deburring and surface energy enhancement, meeting the requirements for subsequent bonding. The treatment effect meets the following criteria: Deburring rate: ,in The total number of burrs with a height ≥ 0.01 mm before deburring. This represents the number of burrs remaining after deburring. Surface energy: It was detected by contact angle measurement.

[0032] Dry ice blasting process parameter range: blasting pressure Movement speed Nozzle distance Average diameter of dry ice particles .

[0033] like Figure 2 As shown, the relationship between dry ice spraying pressure and deburring rate and PP surface energy is illustrated under fixed conditions: nozzle distance d = 120 mm, dry ice particle diameter s = 400 μm, and spray gun moving speed v = 150 mm / s. The deburring rate increases with increasing spraying pressure, while the surface energy initially increases rapidly and then levels off. When the spraying pressure is in the range of 0.6–0.7 MPa, both a deburring rate ≥ 99.9% and a surface energy ≥ 38 mJ / m² can be simultaneously achieved. 2 The process requirements are the optimal parameter range for integrated dry ice processing.

[0034] Synchronous milling dual positioning feature: The mating end faces of the base and the steel support frame are provided with circumferential anti-fooling and anti-rotation dual positioning features formed by synchronous milling. This embodiment adopts an L-shaped anti-fooling positioning groove, whose alignment... Determined using the following formula: ; in Let be the geometric center coordinates of the L-shaped positioning groove on the PP substrate. The coordinates are the geometric center coordinates of the corresponding positioning groove on the steel support frame. The coordinate system is established with the intersection of the component axis and the mating end face as the origin.

[0035] This positioning feature has both foolproof (preventing incorrect assembly direction) and anti-rotation (preventing relative circumferential rotation) functions. After secondary disassembly and assembly, the alignment accuracy retention rate is ≥95%, and there is no relative rotation when a circumferential torque of 5 N·m is applied.

[0036] Finished product dimensional stability requirements: The finished product must pass a temperature cycling and random vibration test to verify dimensional stability and dimensional change rate. satisfy: ; Experimental conditions: Temperature cycling from -40℃ to 85℃, temperature change rate 5℃ / min, holding at both high and low temperatures for 1 hour each, for a total of 150 cycles; simultaneously superimposed with frequencies from 10 to 55 Hz and a power spectral density of 0.02 g. 2 Random vibrations at / Hz These are the measured dimensions of the PP matrix periphery after cycling.

[0037] Protective pad preparation and assembly method: The preparation and assembly method of this invention is divided into four stages: raw material pretreatment and surface treatment, pre-assembly and finishing, positioning detection and adhesive curing, and finished product detection and warehousing. The specific steps are as follows: like Figure 3 As shown, the entire process of preparing and assembling the protective pad of this invention is divided into four core stages: the first stage is raw material pretreatment and surface treatment, which includes raw material screening, stress relief annealing, rough machining and dry ice integrated treatment; the second stage is pre-assembly and fine machining, the core of which is secondary fine machining under pre-assembly constraints and online precision closed-loop control; the third stage is positioning detection and adhesive curing, including positioning accuracy verification, plasma surface activation and precise adhesive assembly; the fourth stage is comprehensive finished product testing and warehousing, and product delivery is achieved after all performance verifications are completed.

[0038] Phase 1: Raw material pretreatment and surface treatment The core objective of this stage is to ensure batch consistency of raw materials, eliminate internal stress in raw materials, and lay the foundation for subsequent processing.

[0039] S0 Raw Material Pre-screening and Batch Consistency Control: Melt index testing is performed on each batch of glass fiber reinforced PP raw materials, and the melt index deviation is controlled to be ≤±0.5g / 10min; zinc layer thickness uniformity testing is performed on galvanized steel coils, and the zinc layer thickness deviation is ≤±1μm, and unqualified batches are rejected.

[0040] S1 Raw Material Incoming Inspection: Testing the linear expansion coefficient of PP material. hygroscopic expansion coefficient and moisture absorption equilibrium time constant , which serves as the input parameter for the multi-factor compensation formula.

[0041] S1.1 Raw material pre-drying treatment: Place the PP rods in an 85℃ hot air circulating drying oven and dry for 8 hours to reduce the moisture content to below 0.05% to prevent bubbles and deformation during processing.

[0042] S2PP annealing pretreatment: The dried PP rods are placed in an 80℃ constant temperature oven for annealing for 4 hours, and then slowly cooled to 23℃ at a rate of 1℃ / h, and stored in a desiccator for 24 hours to completely eliminate the internal stress and residual moisture of the raw materials.

[0043] S3 steel pretreatment: After the galvanized steel coil is flattened, it is leveled to a flatness of ≤0.05mm. A steel support frame blank with 3 V-shaped positioning notches and annular glue storage groove is obtained by precision stamping process.

[0044] S3.1 Stress-relieving annealing of steel parts: The steel support frame blank is placed in a constant temperature oven at 180℃ for annealing for 2 hours to eliminate the internal stress generated during the stamping process and prevent deformation during subsequent processing and use.

[0045] S3.2 Steel part surface cleaning: Use an ultrasonic cleaner (frequency 40kHz, cleaning time 5min) to clean the steel blanks, remove stamping oil and metal debris, and dry with 80℃ hot air after cleaning.

[0046] S4PP rough machining: PP billet is obtained by CNC turning PP bar stock, with a 0.4mm finishing allowance reserved on the outer perimeter; 3 positioning bosses with elastic barbs are milled on the inner ring, which correspond one-to-one with the V-shaped positioning notches of the steel parts to achieve preliminary positioning during pre-assembly.

[0047] S5 coarse deburring: Use a nylon brush to clean the macroscopic burrs on PP blanks and steel blanks to avoid affecting the subsequent dry ice treatment effect.

[0048] S5.1 Dry ice process parameter pre-calculation: based on nozzle distance Dry ice particle diameter As initial values, combine surface energy To meet the requirement of a deburring rate of ≥99.9%, calculate the injection pressure. With movement speed The theoretical value.

[0049] S5.2 Dry ice process parameter verification: Take 3 PP test pieces from the same batch, perform dry ice treatment according to the theoretical parameters, and test the surface energy and deburring rate; if the requirements are not met, fine-tune the spray pressure (±0.05MPa) or the moving speed (±10mm / s) until the parameters are qualified.

[0050] The final parameters for the S6 dry ice process were determined: Based on the verification results, the dry ice injection pressure, moving speed, nozzle distance, and dry ice particle diameter for this batch were determined, and a process document was created.

[0051] S7 dry ice integrated treatment: Dry ice treatment is performed on all machined surfaces of the PP blank according to the final determined parameters. After treatment, the residual dry ice debris and dust on the surface are blown away with 0.2MPa compressed air.

[0052] S7.1 Dry ice treatment effect test: Randomly select 5% of PP blanks and test their surface energy and deburring rate; unqualified parts are re-treated with dry ice until they meet the requirements.

[0053] Phase Two: Pre-assembly and Finishing The core objective of this stage is to achieve secondary finishing under pre-assembly constraints, ensuring dimensional accuracy and alignment of positioning features.

[0054] S8 pre-assembly press fitting: A servo press is used to press the steel support frame into the inner ring of the PP blank at a uniform speed of 5mm / s. After the positioning boss is fully engaged in the V-shaped positioning notch, the pressure is held for 10s. The axial movement of the component is detected to be ≤0.02mm, and the pre-assembled component is obtained.

[0055] S8.1 Real-time monitoring of pressing force: The pressing force curve is collected in real time during the pressing process. The peak pressing force should be controlled within the range of 80 to 120 N. If the peak value is too high, it indicates that the interference is too large, which is easy to cause cracking of the PP matrix. If the peak value is too low, it indicates that the interference is insufficient, which is easy to cause loosening. Components that exceed the range are marked as unqualified.

[0056] S9 Pre-assembled Component Modal Testing: The pre-assembled components were subjected to modal testing using the impact test method to identify the first-order natural frequencies. ;like This indicates that the component joint stiffness is insufficient, and the pressing force needs to be adjusted and the component re-pressed.

[0057] S9.1 Modal Analysis: For components with a first-order natural frequency close to 200Hz, further analyze their mode shapes; if the mode shape shows relative torsion between the PP matrix and the steel support frame, it indicates poor pre-assembly positioning and requires re-pressing.

[0058] S10 Secondary Clamping and Alignment: The pre-assembled components are clamped onto the five-axis CNC machine, with the inner hole and end face of the steel support frame as the positioning reference (small deformation of steel parts and high positioning accuracy), and the alignment accuracy is ≤0.005mm.

[0059] S10.1 Clamping Deformation Detection: After clamping, use a dial indicator to check the deformation of the PP substrate end face. Subsequent processing can only proceed if the deformation is ≤0.003mm. If the deformation is too large, the clamping force needs to be adjusted or the substrate needs to be re-clamped.

[0060] S11 machining dimension calculation: Substitute the current batch... , , Ambient temperature and humidity, distance from dry ice nozzle Based on the dimensional deviation feedback value from the previous batch, the target machining dimension is calculated using a multi-factor coupling compensation formula. Import the CNC machining program.

[0061] Among them, the dimensional deviation feedback value of the previous batch is the sum of the values ​​of all qualified parts in the previous batch. average And Bayesian optimization was used to adjust the compensation coefficient over five consecutive batches. Perform a smooth update using the following formula: ; Learning rate The value should be between 0.02 and 0.08 to avoid size fluctuations caused by sudden changes in the compensation coefficient.

[0062] S11.1 Machining parameter optimization: Based on the cutting performance of PP material, the cutting speed is determined to be 120-150 m / min, the feed rate is 0.1 mm / r, and the depth of cut is 0.2 mm; carbide tools are used to reduce the impact of tool wear on dimensional accuracy.

[0063] S12 Simultaneous Finishing: Turning the outer circumferential surface of the PP substrate to the target dimension using optimized machining parameters. Subsequently, under the same clamping condition, the L-shaped anti-foolproof positioning grooves on the same end face of the PP substrate and the steel support frame are milled simultaneously to ensure the absolute alignment of the positioning features of the two.

[0064] S12.1 Processing temperature monitoring: Use an infrared thermometer to monitor the temperature of the cutting area in real time. If the temperature exceeds 60℃, pause processing and wait for the temperature to drop below 40℃ before resuming to prevent thermal deformation of PP material from affecting processing accuracy.

[0065] S13 Online Accuracy Inspection and Feedback: The outer perimeter dimensions of the PP substrate are detected in real time using a laser diameter gauge. If the deviation exceeds ±0.01mm, the part is marked and the compensation coefficient is triggered. The adaptive correction is given by the following formula: ; Correction coefficient Take 0.05.

[0066] S13.1 Real-time Temperature Compensation: During online detection, the ambient temperature is collected synchronously. Temperature compensation is applied to the measurement results of the laser diameter gauge. The compensation formula is as follows: ; in The linear expansion coefficient of the optical glass in the laser diameter gauge is given by [value]. .

[0067] S13.2 Dimensional Deviation Statistical Analysis: Perform statistical analysis on the dimensional deviations of all processed parts in this batch, and calculate the average value and standard deviation; if the standard deviation exceeds 0.005mm, it indicates that the processing process is unstable and the CNC machining parameters need to be adjusted.

[0068] S14 Stress Release and Micro-Vibration Aging: The finished components are placed in an environment of 23±1℃ and 45±5%RH, and micro-vibration with a frequency of 20~50Hz and an amplitude of 0.08mm is applied for 6 hours to accelerate the release of machining stress.

[0069] S14.1 Vibration Aging Energy Density Control: During the vibration aging process, the vibration energy density is input. Should meet: ; Ensure that stress is fully released without causing new deformation.

[0070] S14.2 Real-time monitoring of dimensional stability: The outer perimeter of the component is checked every 2 hours. The change in dimensional stability is ≤0.005mm after two consecutive measurements. If the requirement is not met after 6 hours, the vibration aging time is extended to 8 hours.

[0071] Phase Three: Positioning Detection and Adhesive Curing The core objective of this stage is to ensure positioning accuracy and improve the bonding strength between PP and steel components.

[0072] S15 Positioning Accuracy Inspection: The alignment of the L-shaped foolproof positioning groove is inspected using a coordinate measuring machine. ,Require Defective parts are repaired by slightly milling the positioning grooves.

[0073] S15.1 Anti-rotation performance test: For components with qualified positioning accuracy, apply a circumferential torque of 5 N·m and test whether relative rotation occurs; no rotation is considered qualified.

[0074] S16 Disassembly, Cleaning, and Plasma Activation: The pre-assembled components are disassembled along the axial direction, and the mating surfaces are wiped with anhydrous ethanol to remove oil and dust. Subsequently, the inner ring surface of the PP matrix is ​​subjected to atmospheric pressure plasma treatment with a power of 300W and a treatment time of 10s to further enhance the surface energy.

[0075] S16.1 Plasma treatment uniformity test: Nine points (one at the center and eight at the edge) are selected evenly on the inner surface of the PP matrix using a contact angle measuring instrument to test the surface contact angle. A contact angle deviation of ≤±2° is considered to be in good uniformity.

[0076] S16.2 Surface Energy Verification: After plasma treatment, the surface energy of the inner ring surface of the PP matrix should be ≥60mJ / m 2 Non-conforming parts are re-treated with plasma.

[0077] S17 Automatic Adhesive Application: An adhesive dispensing robot is used to uniformly apply acrylic structural adhesive to the mating surfaces of the steel support frame, with the adhesive layer thickness controlled between 0.03 and 0.05 mm.

[0078] S17.1 Adhesive layer thickness uniformity control: During the dispensing process, the dispensing speed With glue output The following relationship must be satisfied: ; in This is the volume correction factor for the adhesive solution (0.95~1.05). For the width of the adhesive application, The target adhesive layer thickness.

[0079] S17.2 Adhesive application quality inspection: The continuity and integrity of the adhesive application trajectory are detected by a visual inspection system. No glue breaks or overflows are considered qualified.

[0080] S18 Secondary Assembly and Pressure Holding: Strictly press the steel support frame into the PP matrix according to the corresponding position of the L-shaped anti-foolproof positioning groove, and apply 0.2MPa axial pressure for 30min.

[0081] S18.1 Control of adhesive overflow during press-fitting: During press-fitting, the amount of adhesive overflow should be controlled within 80% to 100% of the volume of the annular adhesive reservoir. Insufficient overflow indicates that the amount of adhesive is too small, which is prone to bonding defects. Excessive overflow indicates that the amount of adhesive is too large, which is prone to contaminating other surfaces. Components exceeding the range are marked as unqualified.

[0082] S18.2 Real-time monitoring of adhesive layer curing: The adhesive layer curing process is monitored in real time using an ultrasonic flaw detector. The pressure holding can only be released when the adhesive layer curing degree reaches more than 90%.

[0083] S18.3 Excess Adhesive Cleaning: After the pressure holding is completed, use a special plastic scraper to clean up any excess adhesive that has overflowed, ensuring that there is no residual adhesive on the mating surfaces.

[0084] S18.4 Static Curing: After removing excess adhesive, place the module in an environment of 23±1℃ and 45±5%RH for 2 hours until the adhesive layer is completely cured.

[0085] Phase Four: Finished Product Inspection and Warehousing The core objective of this phase is to comprehensively verify the performance of the finished product and ensure product quality.

[0086] S19 Finished Product Inspection: After secondary assembly, the alignment error of the L-shaped anti-foolproof positioning groove is re-inspected to be ≤0.03mm; and temperature cycling and random vibration verification are performed under the aforementioned conditions to verify the dimensional change rate. .

[0087] S19.1 Pull-out force test: Randomly select 1% of the finished products and use a universal testing machine to test the axial pull-out force. A pull-out force ≥120N is considered qualified.

[0088] S19.2 Sealing test: Assemble the protective gasket onto the standard air conditioner housing, apply a pressure difference of 500Pa, and use a flow sensor to detect the leakage. The leakage is considered qualified if it is ≤0.5L / min.

[0089] S19.3 Debris blocking efficiency test: Standard dust with a particle size of 0.3 to 0.5 mm is used for testing. A debris blocking efficiency of ≥99.95% is considered qualified.

[0090] S19.4 Sound insulation performance test: The sound insulation of the protective pad at a frequency of 2000Hz is tested using a sound level meter. A sound insulation of ≥3dB is considered qualified.

[0091] S19.5 Appearance Inspection: The appearance of the finished product is inspected using a visual inspection system. The product is considered qualified if there are no defects such as scratches, deformation, missing materials, or glue stains.

[0092] S20 Packaging and Warehousing: All qualified finished products are individually packaged in anti-static bags, labeled with the product model, batch number and production date, and then stored in the warehouse.

[0093] Specific embodiment: The protective pad prepared in this embodiment is used at the connection between the air conditioner fan and the housing of a new energy vehicle, with a nominal outer diameter of... It has an inner diameter of 20mm and a thickness of 5mm. The specific manufacturing process is as follows: Raw material parameters confirmed: Glass fiber reinforced PP matrix: 12wt% glass fiber reinforced PP rods of grade PP-GF12 were used. The melt flow index was tested to be 11.8 g / 10 min (deviation ±0.3 g / 10 min), and the coefficient of linear expansion was [not specified]. hygroscopic expansion coefficient Moisture absorption equilibrium time constant Tensile strength 38MPa, heat distortion temperature 125℃.

[0094] Galvanized steel support frame: DX51D+Z grade galvanized steel coils are used, with an average zinc layer thickness of 10μm (deviation ±0.7μm), and no red rust is observed after 48 hours of salt spray testing.

[0095] Raw material pretreatment and surface treatment: Perform the steps S0-S7.1 as described above, with the specific process parameters as follows: PP pre-drying: hot air drying at 85℃ for 8 hours, final moisture content 0.03%; PP annealing: maintain a constant temperature of 80℃ for 4 hours, then decrease the temperature to 23℃ at a rate of 1℃ / h, and store in a desiccator for 24 hours; Steel stamping: Level to a flatness of 0.03mm, and stamp out a rough blank with 3 V-shaped positioning notches and an annular glue storage groove (depth 0.15mm, width 0.5mm); Stress relief for steel parts: Annealing at 180℃ for 2 hours, ultrasonic cleaning at 40kHz for 5 minutes, and then drying at 80℃. PP rough machining: CNC turning to an outer diameter of 50.4mm, and milling three positioning bosses with elastic barbs on the inner ring; Dry ice process parameters: injection pressure 0.6MPa, moving speed 150mm / s, nozzle distance 120mm, particle diameter 400μm; after treatment, the detected deburring rate is 99.96%, and the surface energy is 41mJ / m 2 , all are qualified.

[0096] Pre-assembly and finish machining: Pre-assembly press-fitting: the servo press performs press-fitting at a speed of 5mm / s, with pressure holding for 10s, axial play of 0.01mm, and peak press-fitting force of 92N; Modal test: the first-order natural frequency is 235Hz, there is no relative torsion in the vibration mode, and it is qualified; Secondary clamping and alignment: taking the inner hole and end face of the steel frame as the reference, the alignment accuracy is 0.003mm, and the clamping deformation is 0.002mm; Calculation of target machining size: substituting parameters gives ; Synchronous finish machining: cutting speed 130m / min, feed rate 0.1mm / r, depth of cut 0.2mm, turning the outer diameter to 49.985mm, synchronously milling the L-shaped fool-proof positioning groove; the maximum temperature in the cutting area is 51℃; On-line detection: the size deviation detected by the laser diameter measuring instrument is ±0.007mm, the deviation after compensation at an ambient temperature of 24℃ is ±0.006mm, and the batch size standard deviation is 0.003mm; Micro-vibration stress relief: frequency 30Hz, amplitude 0.025mm, duration 6h, vibration energy density 12150mm 2 ・Hz 2 ・s; the size is detected every 2h, the continuous change for two times is ≤0.003mm, and it is qualified.

[0097] Positioning detection and adhesive bonding curing: Positioning accuracy detection: the alignment of the L-shaped groove measured by the three-coordinate measuring machine is 0.011mm, and there is no relative rotation when a torque of 5N・m is applied; Plasma activation: treatment at 300W power for 10s, the contact angle deviation of 9 points is ±1.2°, the surface energy is 66mJ / m 2 ; Automatic gluing: 3MDP8005 acrylic structural adhesive is coated, the adhesive layer thickness is 0.04mm, the dispensing speed is 50mm / s, and visual inspection confirms no adhesive breakage or adhesive overflow; Secondary assembly and pressure holding: pressure holding at 0.2MPa for 30min, the adhesive overflow amount accounts for 88% of the volume of the adhesive storage tank, the pressure holding is released after ultrasonic detection confirms the curing degree is 93%, and the product is left standing for 2h to be fully cured after cleaning the overflowed adhesive.

[0098] Finished product performance detection: Dimension re-inspection: alignment error of the L-shaped groove is 0.014mm; Environmental reliability test: After 150 cycles of temperature cycling from -40℃ to 85℃, superimposed with random vibration, the measured outer diameter was 49.983 mm, and the dimensional change rate was... ; Pull-out force: Randomly sampled 1% of finished products, the average axial pull-out force was 138N; Sealing performance: Leakage rate of 0.28 L / min under a pressure difference of 500 Pa; Debris blocking efficiency: 99.98%; Sound insulation: 3.7dB at 2000Hz; Appearance: No scratches, deformation, glue stains or other defects.

[0099] The protective pad prepared in this embodiment has a gap of ≤0.06mm between it and the air conditioner housing after assembly, and the airflow disturbance reduction rate is 21%. All performance indicators are better than the industry standard and fully meet the usage requirements of new energy vehicle air conditioning systems for more than 10 years.

[0100] like Figure 4 As shown, the key performance comparison results between the process of this invention and the traditional PP-steel composite protective pad process are as follows: the dimensional deviation is reduced from ±50μm to ±10μm in the traditional process, with a 5-fold improvement in accuracy; the axial pull-out force is increased from 80N in the traditional process to over 120N, with an improvement of ≥50%; the positioning alignment error is reduced from 50μm to ≤2μm in the traditional process, with a 25-fold improvement in accuracy; and the dimensional change rate after 150 cycles of high and low temperature superimposed random vibration is reduced from 0.5‰ in the traditional process to 0.05‰, with a 10-fold improvement in dimensional stability, achieving a significant breakthrough in overall performance.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A protective pad composed of PP parts and steel parts, comprising a glass fiber reinforced PP matrix and a galvanized steel support frame interference-fitted into the inner ring of the PP matrix, characterized in that: The outer peripheral surface of the PP matrix is ​​a multi-factor compensated dimensional surface formed by secondary precision machining under pre-assembly constraint state. All machined surfaces of the PP matrix are treated with dry ice deburring and surface activation in one process. The mating end faces of the PP substrate and the steel support frame are provided with circumferential anti-foolproof and anti-rotation dual positioning features formed by synchronous milling. The alignment error of the dual positioning features is ≤0.02mm, and the alignment accuracy retention rate after secondary disassembly and assembly is ≥95%.

2. A protective pad composed of PP parts and steel parts according to claim 1, characterized in that, The target machining dimension of the multi-factor compensated dimension surface Calculated using the following multi-factor coupling compensation formula: ; in: The nominal design dimensions are for the outer peripheral surface of the PP substrate; Design tolerance for the outer peripheral surface of the PP substrate in one direction; The coefficient of linear expansion of glass fiber reinforced polypropylene (PP) is given, with a range of values. ; The total temperature difference between the machining environment and the vehicle's maximum operating limits; The equivalent temperature difference coefficient is used to account for non-uniform thermal expansion; This represents the maximum stress-release deformation of PP after machining under constrained conditions. This is the compensation amount for time-dependent moisture absorption expansion deformation. , RH represents the hygroscopic expansion coefficient of PP, and RH represents the annual average relative humidity of the operating environment. The PP moisture absorption equilibrium time constant is taken as 120–180 h. This refers to the cumulative duration of use of the protective mat since it was put into service. This is the dimensional compensation amount resulting from nozzle distance correction. , The vertical distance from the dry ice spray nozzle to the PP substrate surface is in mm. The value represents the amount of microplastic deformation on the PP surface caused by dry ice deburring, ranging from 0.01 to 0.02 mm. The apparent size reduction caused by the micro-nano texture formed by dry ice surface activation is 0.005–0.01 mm. This is the deformation compensation correction coefficient, with a value ranging from 0.1 to 0.

2.

3. A protective pad composed of PP parts and steel parts according to claim 2, characterized in that, The integrated dry ice deburring and surface activation treatment meets the following criteria: ; in, The total number of burrs with a height ≥ 0.01 mm before deburring. This represents the number of burrs remaining after deburring. This refers to the dry ice injection pressure. The speed of the dry ice spray gun is measured in mm / s. This represents the vertical distance from the nozzle to the PP substrate surface, in mm. The value range is 100–150 mm; The value represents the average diameter of the dry ice particles, expressed in μm, and ranges from 300 to 500 μm.

4. A protective pad composed of PP parts and steel parts according to claim 3, characterized in that, The dual positioning feature is an L-shaped anti-foolproof positioning groove, and its alignment... The determination is made using the following formula: ; in, Let be the geometric center coordinates of the L-shaped positioning groove on the PP substrate. The coordinates are the geometric center coordinates of the L-shaped positioning groove on the steel support frame. The coordinate system is established with the intersection of the component axis and the mating end face as the origin.

5. A protective pad composed of PP parts and steel parts according to claim 4, characterized in that, The finished product's dimensional stability must meet the following criteria: ; The temperature cycling conditions were as follows: within the range of -40℃ to 85℃, the temperature change rate was 5℃ / min, with each high and low temperature held for 1 hour, for a total of 150 cycles; and during the cycling process, a frequency of 10–55 Hz and a power spectral density of 0.02 g were superimposed. 2 Random vibrations at / Hz The measured dimensions of the PP matrix periphery after cycling are shown.

6. A protective pad composed of PP parts and steel parts according to claim 5, characterized in that, Its preparation and assembly methods include four stages: raw material pretreatment and surface treatment, pre-assembly and finishing, positioning detection and bonding curing, and finished product detection and warehousing.

7. The assembly method of a protective pad composed of PP parts and steel parts according to claim 6, characterized in that, The raw material pretreatment and surface treatment stage includes the following steps: S0 Raw Material Pre-screening and Batch Consistency Control: Melt index testing is performed on each batch of glass fiber reinforced PP raw materials, and the melt index deviation is controlled to be ≤ ±0.5g / 10min; zinc layer thickness uniformity testing is performed on galvanized steel coils, and the zinc layer thickness deviation is ≤ ±1μm; S1 Raw Material Incoming Inspection: Testing the linear expansion coefficient of PP material. hygroscopic expansion coefficient and moisture absorption equilibrium time constant , as the input parameter of the compensation formula; S1.1 Raw material pre-drying treatment: Place the PP rods in an 85℃ hot air circulating drying oven and dry for 8 hours to reduce the moisture content to below 0.05%; S2PP annealing pretreatment: The dried PP rods are placed in an 80℃ constant temperature oven for annealing for 4 hours, and then cooled to 23℃ at a rate of 1℃ / h and stored in a desiccator for 24 hours to completely eliminate internal stress and residual moisture. S3 steel pretreatment: After the galvanized steel coil is flattened, it is leveled to a flatness of ≤0.05mm, and stamped to obtain a steel support frame blank with 3 V-shaped positioning notches and an annular glue storage groove; S3.1 Stress-relieving annealing of steel parts: Place the steel support frame blank in a constant temperature oven at 180℃ for annealing for 2 hours to eliminate the internal stress of stamping; S3.2 Steel Surface Cleaning: Use an ultrasonic cleaner to clean the steel support frame blank to remove stamping oil and metal debris, and then dry it with hot air. S4PP rough machining: PP billet is obtained by CNC turning PP bar stock. A 0.4mm finishing allowance is reserved on the outer perimeter. Three positioning bosses with elastic barbs are milled on the inner ring, which correspond one-to-one with the V-shaped positioning notch of the steel part. S5 coarse deburring: Use a nylon brush to clean the macroscopic burrs on the PP blank and the steel support frame blank; S5.1 Pre-calculation of dry ice process parameters: According to the surface energy formula in claim 3, with mm μm is the initial value, and the following equations are combined... Select injection pressure With movement speed Theoretical value; S5.2 Dry ice process parameter verification: Take 3 PP test pieces, perform dry ice treatment according to theoretical parameters, and test the surface energy and deburring rate. If the requirements are not met, fine-tune the parameters until they are qualified. The final S6 dry ice process parameters were determined: Based on the verification results, the dry ice injection pressure for this batch was determined. Movement speed Nozzle distance and the diameter of dry ice particles ; S7 dry ice integrated treatment: Dry ice treatment is performed on the machined surface of the PP blank according to the final determined parameters, and the residual debris is blown away with 0.2MPa compressed air after treatment. S7.1 Dry ice treatment effect test: Randomly select 5% of PP blanks, test surface energy and deburring rate, and reprocess unqualified parts.

8. The assembly method of a protective pad composed of PP parts and steel parts according to claim 7, characterized in that, The pre-assembly and finishing stage includes the following steps: S8 pre-assembly press fitting: A servo press is used to press the steel support frame into the inner ring of the PP blank at a speed of 5mm / s. After the positioning boss is engaged with the positioning notch, the pressure is held for 10s. The axial movement is checked to be ≤0.02mm, and the pre-assembled component is obtained. S8.1 Real-time monitoring of pressing force: The pressing force curve is collected in real time during the pressing process. The peak pressing force should be controlled within the range of 80 to 120 N. Components that exceed the range are marked as unqualified. S9 Pre-assembled Component Modal Testing: Impact modal testing is performed on the pre-assembled components to identify their first-order natural frequencies. ,like If the pressure is Hz, adjust the pressing force and press again; S9.1 Modal Analysis: For components with a first natural frequency close to 200Hz, analyze their mode shapes. If the mode shape shows relative torsion between the PP matrix and the steel support frame, then re-press-fit. S10 Secondary Clamping and Alignment: Clamp the pre-assembled components onto the five-axis CNC machine, using the inner hole and end face of the steel support frame as the positioning reference, with an alignment accuracy of ≤0.005mm; S10.1 Clamping Deformation Detection: After clamping, use a dial indicator to check the deformation of the PP substrate end face. Subsequent processing can only proceed if the deformation is ≤0.003mm. S11 Machining Dimension Calculation: Substitute the multi-factor coupling compensation formula according to claim 2 into the current batch... , , Ambient temperature and humidity, distance from dry ice nozzle Calculate the target machining dimension based on the dimensional deviation feedback value from the previous batch. Import the CNC machining program; S11.1 Machining parameter optimization: Based on the machinability of PP material, the cutting speed is determined to be 120-150 m / min, the feed rate is 0.1 mm / r, and the depth of cut is 0.2 mm; S12 Synchronous Finishing: Turning the outer circumferential surface of the PP substrate to the desired depth using optimized machining parameters. Then, simultaneously mill the L-shaped anti-foolproof positioning groove on the same end face of the PP substrate and the steel support frame; S12.1 Process temperature monitoring: Use an infrared thermometer to monitor the temperature of the cutting area in real time. If the temperature exceeds 60℃, pause the process and resume when the temperature drops below 40℃. S13 Online Accuracy Inspection and Feedback: The outer perimeter dimensions of the PP substrate are detected in real time using a laser diameter gauge. If the deviation exceeds ±0.01mm, the part is marked and the compensation coefficient is triggered. The adaptive correction is given by the following formula: , Take 0.05; S13.1 Real-time Temperature Compensation: During online detection, the ambient temperature is collected synchronously. Temperature compensation is applied to the measurement results of the laser diameter gauge. The compensation formula is as follows: ,in The linear expansion coefficient of the optical glass in the laser diameter gauge is given by [value]. ; S13.2 Dimensional Deviation Statistical Analysis: Perform statistical analysis on the dimensional deviations of all machined parts in this batch, calculate the average value and standard deviation. If the standard deviation exceeds 0.005mm, adjust the CNC machining parameters. S14 Stress Relief and Micro-Vibration Aging: The finished components were placed in an environment of 23±1℃ and 45±5%RH and subjected to micro-vibration with a frequency of 20~50Hz and an amplitude of 0.08mm for 6 hours. S14.1 Vibration Aging Energy Density Control: During the vibration aging process, the vibration energy density is input. Should meet ,in Amplitude (unit: mm) Vibration frequency (unit: Hz) The vibration time is expressed in seconds. S14.2 Real-time monitoring of dimensional stability: The outer circumference dimension is checked every 2 hours. The change in the dimension is ≤0.005mm after two consecutive measurements. If the requirement is not met after 6 hours, the vibration aging time is extended to 8 hours.

9. The assembly method of a protective pad composed of PP parts and steel parts according to claim 8, characterized in that, The positioning detection and adhesive curing stage includes the following steps: S15 Positioning Accuracy Detection: Detect the alignment of the L-shaped anti-foolproof positioning groove according to the formula in claim 4. mm, if it is not up to standard, it will be reworked; S15.1 Anti-rotation performance test: For components with qualified positioning accuracy, apply a circumferential torque of 5 N·m and test whether relative rotation occurs. If no rotation occurs, it is qualified. S16 Disassembly, Cleaning and Plasma Activation: The pre-assembled components are disassembled along the axial direction. After wiping the mating surfaces with anhydrous ethanol, the inner ring surface of the PP matrix is ​​treated with atmospheric pressure plasma at a power of 300W for 10s. S16.1 Plasma treatment uniformity test: Nine points are evenly selected on the inner ring surface of the PP matrix using a contact angle measuring instrument, and the surface contact angle is measured. The uniformity is qualified if the contact angle deviation is ≤ ±2°. S16.2 Surface Energy Verification: After plasma treatment, the surface energy of the inner ring surface of the PP matrix should be ≥60mJ / m 2 Defective parts are re-treated with plasma. S17 Automatic Adhesive Application: An adhesive dispensing robot is used to uniformly apply acrylic structural adhesive to the mating surfaces, with the adhesive layer thickness controlled between 0.03 and 0.05 mm. S17.1 Adhesive layer thickness uniformity control: During the dispensing process, the dispensing speed... With glue output satisfy ,in This is the volume correction factor for the adhesive solution, with a value ranging from 0.95 to 1.

05. This refers to the width of the adhesive application, in mm. The target adhesive layer thickness is expressed in mm. S17.2 Adhesive application quality inspection: The continuity and integrity of the adhesive application trajectory are detected by a visual inspection system. No adhesive breaks or overflows are considered qualified. S18 Secondary Assembly Pressure Holding: Press the steel support frame into the PP matrix according to the corresponding position of the L-shaped anti-foolproof positioning groove, apply 0.2MPa axial pressure and hold for 30min; S18.1 Control of adhesive overflow during pressing: During the pressing process, the amount of adhesive overflow should be controlled within 80% to 100% of the volume of the annular adhesive storage tank. Insufficient or excessive overflow is marked as unqualified. S18.2 Real-time monitoring of adhesive layer curing: The adhesive layer curing process is monitored in real time using an ultrasonic flaw detector. The pressure holding can only be released when the adhesive layer curing degree reaches more than 90%. S18.3 Excess Adhesive Cleaning: After the pressure holding is completed, use a special tool to clean up any excess adhesive that has overflowed, ensuring that there is no residual adhesive on the mating surfaces; S18.4 Static Curing: After removing excess adhesive, place the module in an environment of 23±1℃ and 45±5%RH for 2 hours until the adhesive layer is completely cured.